Removal of Lead(II) from Water by Adsorption on Novel Composites of Polyaniline with Maize Bran, Wheat Bran and Rice Bran - Kanwal, Farah; Rehman, Rabia; Anwar, Jamil; Saeed, Muhammad (Asian Journal of Chemistry, 2012)
Polyaniline composites are gaining importance now-a-days for waste water treatment by adsorption. In this research work, novel composites of polyaniline with maize bran, wheat bran and rice bran have been synthesized, characterized and employed for batch wise adsorption of Pb(II) from water. FT-IR technique was used for surface analysis of adsorbents. Various operational conditions of adsorption process like agitation time, pH, adsorbent dose, particle size of composites and temperature were optimized for isothermal and thermodynamical investigations. Maximum adsorption capacity values for polyaniline composites with maize bran, wheat bran and rice bran were 18.75, 28.93 and 30.11 mg/g of adsorbent, respectively. Negative DGº values for adsorption of Pb(II) on these composites showed spontaneity of adsorption process. These results showed that maize bran, wheat bran and rice bran modified the external morphology of polyaniline by precluding its aggregation and enhancing its adsorption capacity.